Beauty of material: selecting timber species for Malay woodcarving - Said, Ismail (Fakulti Alam Bina, UTM, 2004)
Selecting timber species is a significant factor in the making of woodcarving components of Malay architecture and crafts. Three determining factors are observed by Malay craftsmen in the selection of the timber including availability of timber, physical characteristics and durability, and craftsmen’s spiritual beliefs towards the timber species. These criteria address the intrinsic knowledge of the craftsmen upon the beauty and meaning of tropical timbers and hence in the identity of the carving. This knowledge must be address to the people for the appreciation of the carving and possibly taking woodcarving as a job or passion, setting pace for the woodcarving to prevail for many generations to come.